A study of factors influencing rate of gain, quantity of feed consumed and carcass grade, 1947-48. - Bell, F.W.; Mackintosh, D.L.; Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
This is a study of the characteristics of feeder calves which are associated with differences in: 1. Rate of gain. 2. Kind and amount of feeds required to make gain. 3. Value of the carcass. The two lots of calves were selected from 100 range-bred heifer calves purchased in November 1947 for feeding tests at this station. These calves graded good to choice feeders and were quite uniform.
Keywords: Beef; Rate of gain; Carcass grade; Feed consumption